AUDIT PIUTANG USAHA PADA PT. AGUS SUTA LINE DI SAMARINDA - Prawinata, Wijaya Rossa (EKONOMIA, 2014)
The purpose of this study was to determine the fairness of the accounts receivable balance that presented in the financial report of PT. Agus Suta Line. The analysis tools being used was Audit Program and Audit Procedures, also Accounts Receivable Audit Working Papers, by examine the fairness of accounts receivable balance of PT. Agus Suta Line according to audit procedures and audit programs which has been made then followed by the making of audit working paper. Based on the results of a study of the financial statement of PT. Agus Suta Line, it had been found that no material errors in the calculation and recording of accounts receivable balance, but it had been discovered that PT. Agus Suta Line does not calculate allowance for bad debts so that in the financial report does not appear the presentation of allowance for bad debts and the one being presented is the amount of gross accounts receivable, so it is not in accordance with the Financial Accounting StandardsÂ  for Non Public Accountable Entities.